KEEFEKTIFAN PENDEKATAN PEMBELAJARAN WHOLE LANGUAGE DAN PENDEKATAN KOMUNIKATIF TERHADAP KETERAMPILAN MEMBACA DAN MOTIVASI BELAJAR PESERTA DIDIK - Ai Yusi Kurniawati; Sri Dewi Nirmala; Lidwina Sri Ardiasih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the differences between the pretest and post-test results of students' reading abilities, and analyzes the differences between students' reading skills and students’ learning motivation through the Whole Language learning approach and the communicative approach. The research method used is quasi-experimental with data analysis of paired sample t-test for pretest and post-test data and independent sample t-test. The results indicate that the use of the Whole Language learning approach is more effective than the communicative approach on students' reading skills and learning motivation. Thus, the application of the Whole Language learning approach is more recommended than the communicative approach on students' reading skills and learning motivation.